Determinan Integritas Laporan Keuangan Perusahaan Pertambangan di Indonesia - Lilianti, Emma; Mafra, Nisa’Ulul; Putra, Andri Eko (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2023)
This study purpose to determine the effect of leverage, corporate governance, audit committee and company size on the integrity of financial statements. All mining companies on the Indonesia Stock Exchange totaling 63 issuers are a population with a sample selected using purposive sampling of 40 issuers, observation year 2017-2021. The analysis model uses multiple regression to test the direct effect of the independent variable on the dependent variable, after going through the classic assumption testing stages, namely the normality test, autocorrelation test, multicollinearity test and heteroscedasticity test. The results of testing the t hypothesis show that there is a partial and simultaneous effect of leverage, corporate governance, audit committee and company size on the integrity of financial statements.